Health education as education of the oppressed - NC van Wyk (AOSIS, 1999)
Paolo Freire's theory of critical thinking shows remarkable similarities to the principles supported by health education. In his capacity as Brazilian educationalist, Freire emphasized man's active participation in his own development. Without this active involvement, growth and development become quite impossible to attain.